Representasi Pelecehan Seksual di Lingkungan Kerja dalam Film Pendek Please Be Quiet (Analisis Naratif Model Tzvetan Todorov) - Hanyfah, Insyirah; Purwanti, Silviana (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
Please Be Quiet is a movie that reflects cases of sexual harassment in the workplace that refers to a series of events carried out by the perpetrator and his threats, which result in psychological harm to victims and witnesses of sexual harassment. This research aims to find out, analyze, and describe how sexual harassment in the work environment experienced by Putri and Sarah as the sole eyewitnesses of sexual harassment in the film Please Be Quiet. This research uses Tzvetan Todorov's narrative analysis model. Research results from 17 scenes that have been analyzed show that the film Please Be Quiet is a representation of social reality where women as beings who are vulnerable to sexual harassment have a weak position in the work environment. Victims often feel insecure and afraid, they are worried that they will experience bad treatment in the office especially if their boss is a boss who has great power in the workplace. This power makes the employee afraid of losing their job and the career they have built.